1979
DOI: 10.1142/s0192415x79000209
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Stimulation of Ear Acupuncture Points on the Body's Pain Threshold

Abstract: Six ear acupuncture points, one non-acupuncture ear point, and the body locus Ho-Ku (LI-4) were electrically stimulated in order to compare the effects of stimulation on the body's pain threshold at selected loci on various points on the body by measurement with a radiation heat-type Pain Meter on 5 subjects. The ear points, with the exception of the non-acupuncture ear point, were found to be effective even in peripheral body regions in varying degrees. Ear stimulation did not increase the threshold as rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Of the ten studies comparing close to distant needling, eight (80%) showed a larger increase of at least one sensory threshold close to the needling location [35,51,53,67,83,101,102,105]. In six out of eleven studies (54.5%), threshold changes were more pronounced after ipsi-than after contralateral needling [25,34,67,[100][101][102].…”
Section: Effect Of Needle Location Relative To the Sites Of Measurementsmentioning
confidence: 96%
See 4 more Smart Citations
“…Of the ten studies comparing close to distant needling, eight (80%) showed a larger increase of at least one sensory threshold close to the needling location [35,51,53,67,83,101,102,105]. In six out of eleven studies (54.5%), threshold changes were more pronounced after ipsi-than after contralateral needling [25,34,67,[100][101][102].…”
Section: Effect Of Needle Location Relative To the Sites Of Measurementsmentioning
confidence: 96%
“…In nine other studies (18.8%) no effect was observed neither after verum nor after sham acupuncture [22, 27, 42, 47-49, 99, 103, 104], and the results of three studies (6.3%) were rated as unclear [35,44,45]. None of the twelve studies including both control modalities found significant differences between the sham and the inert control group [24,25,27,30,35,42,47,53,57,62,85,99], although in three of these studies, the pre-post comparison indicates larger effects in the sham than in the inert control group [24,30,53,85].…”
Section: Comparison Of Verum Acupuncture To Inert or Sham-control Promentioning
confidence: 96%
See 3 more Smart Citations